Legal Status and Protection for Citizens Against Administrative Decisions - Faliani Zaliaokta; Ghazyan Hidzyam Haqqani; Livia Fajarisalfa; Mudhtia Nabila Maulud; Muhammad Satria Akbar; Taufiq Alamsyah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the legal status of citizens and the legal protection available against State Administrative Decisions within the Indonesian administrative law system. The research addresses three principal issues consisting of the legal position of citizens in administrative disputes, the normative foundations and procedural mechanisms for challenging State Administrative Decisions, and the forms of legal protection together with the legal consequences of Administrative Court judgments. The study employs a normative juridical method supported by statutory, conceptual, and case based approaches. Legal materials were collected through library research involving legislation, judicial decisions, scholarly literature, and legal commentaries. The analysis demonstrates that citizens possess legal standing to challenge administrative decisions when direct and legally recognizable interests are adversely affected. Reviewable administrative decisions must satisfy the requirements of concreteness, individuality, finality, and legal effect, while contemporary developments have expanded reviewable objects to include factual administrative actions and positive fictitious decisions. Legal protection operates through preventive administrative mechanisms and judicial review before the Administrative Court. Administrative Court judgments provide corrective legal remedies through annulment of unlawful decisions, rehabilitation, compensation, and restoration of legal rights. The study concludes that the integration of administrative accountability, judicial control, and effective judgment execution strengthens legal certainty, good governance, and the rule of law within Indonesia’s administrative justice framework.